Implementasi Bahasa Jawa Krama dalam Proses Pembelajaran Anak Usia Dini - Mahla Salsabila; Rohinah Rohinah (Universitas Al-Hikmah Indonesia, 2018)
This research is motivated by the many people who have forgotten and even underestimated Krama Javanese in their daily lives. Parents who prefer to teach Indonesian when at home. Krama Javanese is considered complicated because of the many levels of speech. In addition, parents consider Indonesian language to be easy to understand. Another reason was also expressed by many school institutions using Indonesian as a daily language in interacting everyday. The continuous use of Indonesian will eliminate Javanese Krama language culture especially among students. This research is a qualitative field research and takes the background of applying the learning process using Javanese Krama. The results of this study indicate that (1) the implementation of the Krama Javanese Language in the learning process in group B of the ABA Ngalang Gedangsari Gunungkidul Yogyakarta kindergarten uses habituation, exemplary, and advice methods. The application of the Javanese Krama language is by inserting the Javanese Krama language when interacting, calling, and advising in a language that is easy to understand and does not offend the child. (2) supporting factors include good collaboration between teachers, enthusiasm from teachers, teachers who are not bored to remind children. While the inhibiting factor is that parents do not all apply Javanese Krama when at home and the child's playing environment is not good at speaking.